Impostor Syndrome and Self-Doubt Among High Achievers - Bachi, Doaa M. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Impostor syndrome, also referred to as fraud syndrome, perceived fraudulence, impostor phenomenon, or impostor experience, is a psychological pattern wherein high achievers are unable to internalize their accomplishments. Specific Background: Despite objective indicators of competence and success, individuals experiencing this phenomenon often harbor persistent self-doubt and fear of being exposed as intellectual frauds. Knowledge Gap: Although widely recognized, limited empirical research has systematically explored the cognitive, emotional, and behavioral dimensions of impostor syndrome across diverse professional contexts. Aims: This study aims to investigate the underlying psychological mechanisms of impostor syndrome among high-performing individuals and its impact on mental health, job performance, and professional development.Results: Preliminary findings suggest that impostor syndrome is significantly associated with heightened anxiety, reduced self-efficacy, and increased burnout risk, particularly in competitive and evaluative environments. Novelty: The study offers a multidimensional framework integrating self-perception, external validation, and organizational culture to explain the persistence of impostor experiences among competent professionals. Implications: These insights underscore the need for targeted interventions and workplace policies that address impostor feelings, promote psychological well-being, and foster more inclusive and affirming environments for high-achieving individuals. Highlights: High achievers often struggle with internalizing success. Impostor syndrome is linked to anxiety and burnout. Organizational culture influences impostor experiences. Keywords: Impostor Syndrome, Self-Doubt, High Achievers, Psychological Well-Being, Professional Development